Post-match changes in muscle damage markers among U-21 soccer players - Trajkovic, N.; Sporis, G.; Vlahovic, T.; Madic, D.; Gusic, M. (Montenegrin Journal of Sports Science and Medicine, 2018)
This study aimed to investigate the effect of official soccer matches on selected markers of muscle damage in U-21 soccer players. A group of 19 trained, healthy male soccer players from the junior category took part in this study. Blood samples were assessed pre-match and immediately after a match in response to a competitive (2×45 min) soccer match. Analysis was performed for muscle damage and inflammatory markers. Significant differences between two measures (before and after soccer match) exist in Aspartate-aminotransferase (AST), Lactate dehydrogenase (LDH), and Myoglobin. Plasma K+ significantly decreased after the match (p<0.05), whereas plasma Na+ decreased slightly. This study showed that most selected markers of muscle damage were influenced by a soccer match. However, results remain inconsistent because of the influence of the type, duration, and intensity of exercise. Moreover, some markers show great variability among individuals.